Engagement of CSOs in the Collaborative Governance of Education Policy Process in Cabo Verde - Lopes,José (2021)
Abstract This paper analyses the engagement of Civil Society Organizations (CSOs) in the collaborative governance of education policies in Cabo Verde. In contrast with the mainstream view of CSOs as opposition groups separate from the state, the paper frames them as integrative parts of the collaborative governance process. CSOs’ collaboration with the government in education policy-making generates a (societal linking) social capital in the form of understanding, shared norms, and mutual trust among the various stakeholders within the education system. Such capital is an important resource to guarantee the proficiency and efficiency of education policies.